Rural School Employees' Status, Awareness, and Perceptions of Adult Vaccinations. (August 2013) - Luthy, Karlen E.; Thornton, Eli; Beckstrand, Renea L.; Macintosh, Janelle; Lakin, Richard G.
As key members of the school environment, it is important for school employees to be vaccinated. Employees are in direct contact with children in close quarters for long periods of time and such an environment can easily serve as an outbreak center for vaccine-preventable communicable diseases such as measles. Despite the fact that most school employees believe vaccines are safe and effective and many school employees report they are up-to-date with their vaccines, a closer examination reveals discrepancy between belief and behavior. This research study evaluates the vaccination status, awareness, and perceptions of school employees located in a large rural school district in Utah. As a vaccine advocate, the school nurse can be influential in providing adult vaccination education for school employees, thus increasing awareness of the importance of adult vaccines and knowing one's vaccination status. Additionally, school nurses might need to meet with school district policy makers to promote vaccine mandates for school employees and to assist in the creation of containment plans in the event of a measles outbreak at school.